Cost-effectiveness of insulin detemir compared with NPH insulin in people with type 2 diabetes in Denmark, Finland, Norway, and Sweden. Issue 4 (April 2013) - Ridderstråle, Martin; Jensen, Marie Markert; Gjesing, Rasmus Prior; Niskanen, Leo
Abstract Objective: To assess the cost-effectiveness of insulin detemir compared with Neutral Protamine Hagedorn (NPH) insulin when initiating insulin treatment in people with type 2 diabetes mellitus (T2DM) in Denmark, Finland, Norway, and Sweden. Methods: Efficacy and safety data were derived from a 20-week multi-centre randomized controlled head-to-head clinical trial comparing insulin detemir and NPH insulin in insulin naïve people with T2DM, and short-term (1-year) cost effectiveness analyses were performed. As no significant differences in HbA1c were observed between the two treatment arms, the model was based on significant differences in favour of insulin detemir in frequency of hypoglycaemia (Rate-Ratio = 0.52; CI = 0.44–0.61) and weight gain (Δ = 0.9 kg). Model outcomes were measured in Quality Adjusted Life Years (QALYs) using published utility estimates. Acquisition costs for insulin and direct healthcare costs associated with non-severe hypoglycaemic events were obtained from National Health Service public sources. One-way and probabilistic sensitivity analyses were performed. Results: Based on lower incidence of non-severe hypoglycaemic events and less weight gain, the QALY gain from initiating treatment with insulin detemir compared with NPH insulin was 0.01 per patient per year. Incremental cost-effectiveness ratios for the individual countries were: Denmark, Danish Kroner 170, 852 (€22, 933); Finland, €28, 349; Norway, Norwegian Kroner 169, 789 (€21, 768); and Sweden, Swedish Krona 226, 622 (€25, 097) per QALY gained. Possible limitations of the study are that data on hypoglycaemia and relative weight benefits from a clinical trial were combined with hypoglycaemia incidence data from observational studies. These populations may have slightly different patient characteristics. Conclusions: The lower risk of non-severe hypoglycaemia and less weight gain associated with using insulin detemir compared with NPH insulin when initiating insulin treatment in insulin naïve patients with type 2 diabetes provide economic benefits in the short-term. Based on cost/QALY threshold values, this represents good value for money in the Nordic countries. Using a short-term modelling approach may be conservative, as reduced frequency of hypoglycaemia and less weight gain may also have positive long-term health-related implications.